The SDS and steel surface interaction behaviour in case of high mass flux spray cooling from very high temperature. (15th August 2019) - Das, Lily; Swain, B.; Munshi, B.; Mohapatra, S.S.; Behera, A.
Highlights: The role of additive in surface reaction of steel quenched from a very high temperature is significant. Due to surface reaction new compounds such as FeS, C6 Cr23, Fe2 O3, Na2 S2 O2, NaFeS2, MnO(OH) and Na2 O2 form. For the formation of each new compound the kinetics and reaction mechanism are proposed and validated. Abstract: The use of additives as a coolant enhances the heat transfer rate as it alters the thermo physical properties of the fluid in the favourable direction of heat transfer. Although the aforesaid technology mitigate the requirements depicted in Time Temperature Transformation diagram; however, the quenching from high temperature, which may lead to a reaction with coolant, deposition and modification of surface morphology has not been addressed in the open literature. Therefore, in the current work, the interaction of coolant with the surface has been tried to disclose in terms of surface reaction, deposition or physical changes leading to variation in morphology. In the current work, AISI 304 steel plates are quenched by water with varied concentration of SDS to mitigate the cooling requirement and by using EDS, XRD and SEM analysis, the surface interaction is revealed. The elemental analysis by EDS and XRD clearly indicate the formation of new compounds resulted from the reaction between hot steel and the coolant. Based on the identified compounds formed on the surface, the possible reactions on the surface due to interaction among the hot surface, water, oxygen and adsorbed SDS are proposed and also validated.